PRINCIPLES OF TERMINATION CONTROL OF UNMANNED AERIAL VEHICLES FLIGHT PATH - Kondrashov, Ya.V.; Arutyunyan, A.K.; Kravchyshyn, I.O. (Science-based technologies, 2009)
For realization of control of gliding aircraft descend from the flight path to the defined area of the space let’s propose its non autonomous control principle. The method of control is shown, a goal, tasks and command con-trol program are defined.